1991
DOI: 10.1007/bf00167909
|View full text |Cite
|
Sign up to set email alerts
|

Response of mammalian cells to shear stress

Abstract: The influence of shear forces on adherent mammalian cells was investigated by means of a developed flow chamber. The viability of the cells decreased with increasing exposure level and duration. Additional, changes in the morphology of the cells due to the shear forces were observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(54 citation statements)
references
References 6 publications
0
50
0
Order By: Relevance
“…22 )) have detrimental effects on cardiac cells including cell death and apoptosis. When exposed to excessive shear stress, CMs round up and show signs of dedifferentiation 5,6,[23][24][25] .…”
Section: Selecting Culture Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…22 )) have detrimental effects on cardiac cells including cell death and apoptosis. When exposed to excessive shear stress, CMs round up and show signs of dedifferentiation 5,6,[23][24][25] .…”
Section: Selecting Culture Parametersmentioning
confidence: 99%
“…Similarly, perfusion cin the range from 1 to 170 μm s −1 increased the content of DNA, glycosaminoglycans and hydroxyproline of a tissue-engineered cartilage compared to the static controls [28][29][30] . The appropriate average velocities also depend on the cell type being cultivated 23,25 . Although perfusion at 5-110 μm s −1 had beneficial effect on the constructs based on MC3T3-E1 immature osteoblasts-like cells, an average velocity of 560 μm s −1 significantly reduced the viability in the same system 31 .…”
Section: Selecting Culture Parametersmentioning
confidence: 99%
“…Increasing the amount of stress or exposure time to hybridomas was found to increase damage and death rate of the cells (Kretzmer et al, 1990;Peterson et al, 1988) and increased cell detachment (Kretzmer and Schugerl, 1991). The stage of growth of CRL-8018 hybridoma cells (Peterson et al, 1988) and exposure duration and magnitude of shear stress can have an impact on the effect of shear stress on the cell.…”
Section: Introductionmentioning
confidence: 96%
“…Although at large scale this is usually achieved using stirred tanks, where the agitation is provided by an impeller and the aeration by oxygen spargers from the container bottom, 3 it was found that bursting of bubbles at the free surface 4 and excessive shear stresses 5,6 may damage the cells. These reasons kindled the interest in the use of large scale orbital shaken devices up to thousand liters.…”
Section: Introductionmentioning
confidence: 99%